Airborne pollutants as potential triggers of systemic autoimmune rheumatic diseases: a narrative review. Issue 5 (3rd September 2022) - Celen, Hannelore; Dens, Anne-Cathérine; Ronsmans, Steven; Michiels, Stijn; De Langhe, Ellen
ABSTRACT: The pathogenesis of systemic autoimmune rheumatic diseases (SARDs) is complex and remains insufficiently understood. It is commonly accepted that both intrinsic and extrinsic environmental factors interact to induce a self-reactive immune response. Case reports and observational studies have revealed an association between SARDs and specific airborne environmental factors, but the heterogeneity of the published studies hampers clear conclusions. The aim of this review is to provide an overview of the available epidemiological evidence on the relationship between airborne pollutants and SARDs. We performed a narrative review using the PubMed database. Observational studies have shown significant associations between airborne pollutants and SARDs. Cigarette smoking is strongly associated with the development of rheumatoid arthritis (RA) while the association between cigarette smoke and the development of other SARDs remains controversial. For decades, silica exposure has been linked to systemic sclerosis (SSc), RA and systemic lupus erythematosus (SLE). There is also strong evidence for a link between solvents and SSc. Recent observations even suggest that ambient air pollution is associated with the development of SARDs. Some studies have shown associations between asbestos, organic dust, metals and pesticides and SARDs, but more studies are needed to confirm these findings. Increasing evidence has linked airborne pollutants to SARDs. Although more studies are needed to understand the potential mechanisms by which these environmental agents contribute to disease pathogenesis, awareness of the link between environmental agents and SARDs is important to recognize and prevent work-related and environmentally induced diseases.